The Role of Silymarin in Mitigating Inflammation and Cognitive Impairment Induced by Ovariectomy in Wistar Rats - Razieh Moalefshahri; Hossein Javid; Fatemeh Gheybi; Somaye Fallahnezhad; Seyed Isaac Hashemy (Mediators of Inflammation)
Background. Silymarin, a polyphenolic flavonoid found in milk thistle, has been used to treat liver and brain injuries in humans and animals. The study aims to investigate the protective effects of silymarin on spatial and passive avoidance memory, oxidative stress, and inflammatory factors in the brain and liver tissues of ovariectomized (OVX) Wistar rats. Methods. The study involved 30 female Wistar rats divided into control, sham, and three silymarin-treated groups. After ovariectomy, rats underwent CT scan, and some of them were administered silymarin via gavage for 2 months. Memory and learning were assessed using Morris water maze and shuttle box tests. Brain and liver tissues were analyzed for inflammatory factors (IL-1β, TNFα, and IL-6) and oxidative stress markers (CAT, SOD, and MDA) after sacrifice. Results. Silymarin improved spatial memory and fear learning compared to the sham group (P≤0.05 to P≤0.001). It also significantly reduced IL-1β, TNF-α, and IL-6 levels in the cortex, hippocampus, and liver (P≤0.05 to P≤0.0001) and increased CAT and SOD while decreasing MDA levels (P≤0.05 to P≤0.001) compared to control and sham groups. Conclusion. Long-term administration of silymarin extract can improve learning and memory, reverse cognitive impairment caused by ovariectomy, and reduce oxidative stress and inflammatory factors induced by ovariectomy in the liver and brain of Wistar rats. This is due to the reduction in MDA levels and an increase in CAT activity, although silymarin has some effect on SOD at high doses.